2013
DOI: 10.3122/jabfm.2013.06.120340
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Automated Clinical Reminder on Weight Loss in Primary Care

Abstract: Background: Overweight and obese individuals have increased health risks. Clinical reminders positively affect health outcomes in diabetes and osteoporosis, but the effect of automated prompts on weight loss in obesity has not been studied. Our objective was to determine whether an automatic prompt for the clinician to recommend lifestyle changes to patients with a body mass index (BMI) >25 kg/m 2 led to greater weight loss over a 3-to 6-month interval compared with the absence of a clinical reminder.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 22 publications
(20 reference statements)
0
23
0
Order By: Relevance
“…As shown in Table S3, seven studies did not report any patient characteristics . Four studies reported on age and gender but did not provide any information on socio‐economic status (SES) or ethnicity . The remaining studies were more likely to include ethnicity data than data on SES; when reported, studies used a proxy of individual SES such as education or insurance status, rather than a multidimensional marker of SES such as the Index of Multiple Deprivation (IMD)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Table S3, seven studies did not report any patient characteristics . Four studies reported on age and gender but did not provide any information on socio‐economic status (SES) or ethnicity . The remaining studies were more likely to include ethnicity data than data on SES; when reported, studies used a proxy of individual SES such as education or insurance status, rather than a multidimensional marker of SES such as the Index of Multiple Deprivation (IMD)…”
Section: Resultsmentioning
confidence: 99%
“…There were a range of outcomes measured in the 30 studies, although most included at least one of the key outcomes of interest to this review, namely: Discussion of weight (including lifestyle advice); Measuring and recording of weight and/or BMI; and Referral to WMS …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The objective of our study was to investigate the impact of a web‐based decision support tool that alerts providers at well child visits if the patient's BMI is >85th percentile for age and gender on rates of documentation of diagnosis of paediatric obesity and counselling for nutrition and physical activity in primary care sites.…”
Section: Introductionmentioning
confidence: 99%